Prevalence of Hypodontia in Orthodontic Patients at Nobel Medical College, Biratnagar - Acharya, Anand; Giri, Nidhi; Jha, Raj Kumar; Singh, Jitendra (Birat Journal of Health Sciences, 2021)
Introduction: Hypodontia or tooth agenesis is the most common developmental anomaly in craniofacial region. The multitude of problems in patients with hypodontia includes aesthetic, periodontal damage, malocclusion, inarticulate speech and alveolar bone deficiency. This commonly encountered condition in orthodontic department has variable site of occurrence, sometimes associated with syndromes. Objective: To know the patterns and types of hypodontia in orthodontic patients attending orthodontic department at Nobel Medical College, Biratnagar.Methodology: Cross sectional study of 260 orthodontic patients’ pre-treatment records i.e., casts, orthopantomogram, lateral cephalometric radiographs and photographs were taken as study materials. Descriptive statistics was used to analyze the data and chi square test was used to find the level of significance among genders.Results: Congenital absence of one or more teeth was observed in 28 out of 260 patients, with a frequency of 10.8%. Among the hypodontia patients, 11 (4.23%) were males and 17 (6.54%) were females. Of all 69 missing teeth, the most (68%) was observed in class I group, and the least amount belonged to class III group (10%).Conclusions: The higher prevalence of hypodontia in Orthodontic patients in this region warrants careful inspection and investigation before embarking on the diagnosis and treatment planning.